Evaluasi Program Pendidikan Dan Pelatihan Calon Kepala Madrasah Melalui Metode On The Job Training - Diksi Metris; Maman Sulaeman; Nur Mustadjabah (Jurnal Dinamika Ekonomi & Bisnis, 2022)
The implementation of educational and training evaluations (training) on human resources in the educational organization environment is a necessity. The most prominent weakness of resources in the madrasa environment is the managerial competence of the madrasa head which is not supported by adequate educational qualifications and qualified leadership capacity. Another study said the success of a madrasa was an achievement of a madrasa head. The training program for madrasah head candidates with the on the job training method has been officially organized by the Education and Training Center for Education and Technical Personnel training in Education and Religion based on the Regulation of the Minister of Religion (PMA) Number 58 of 201. The results of the study stated that the training program for madrasah head candidates through the on the job training method can be applied and is very good because participants have had good knowledge and skills beforehand which are processed through madrasah leadership practices. Once they follow the training, those skills can be applied and continued. Based on the results of the evaluation through the EVALUATION OF CIPP (Context, Input, Process and Product) shows that the training program for prospective madrasah heads has a high success rate